A new method based on SOM network to generate coarse meshes for overlapping unstructured multigrid algorithm - Lu, Hong-qiang; Wu, Yi-zhao; Chen, Song-can (Applied mathematics and computation, 2003)
A new method to generate coarse meshes for overlapping unstructured multigrid algorithm based on self-organizing map (SOM) neural network is presented in this paper. The application of SOM neural network can overcome some limitations of conventional methods and which is designed to pursuit the best structure relation between fine and coarse unstructured meshes with the object to ensure robust convergence for overlapping unstructured multigrid algorithm. Besides, this method can automate the generation of unstructured meshes and is suitable for both two and three dimensions conditions.